The Internalization of Maqāṣid al-Sharī‘ah Values in Islamic Home Financing through the Ijarah Muntahiyah Bittamlik (IMBT) Scheme - Zamroni, M Afif; Warti’ah, Warti’ah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The rapid development of Islamic finance raises critical questions regarding whether financial products truly reflect the substantive objectives of maqāṣid al-sharī‘ah beyond mere contractual compliance. In particular, the implementation of Ijarah Muntahiyah Bittamlik (IMBT) in Islamic home financing presents both opportunities and challenges in aligning operational mechanisms with ethical and socio-economic objectives. This study aims to analyze the internalization of maqāṣid al-sharī‘ah values within the IMBT scheme and to evaluate its role in promoting financial inclusion, economic justice, and sustainable household welfare. This research employs a qualitative approach using a Systematic Literature Review (SLR) method, synthesizing relevant scholarly works on IMBT, maqasid, and value-based Islamic finance. The analysis focuses on the operational structure of IMBT, its compliance with Sharia principles, and its broader socio-economic implications. The findings indicate that IMBT has the potential to function not only as a Sharia-compliant financing instrument but also as a value-based mechanism that promotes equitable wealth distribution and financial stability. However, the study also reveals that the implementation of maqasid values remains limited due to challenges in governance, regulatory harmonization, and practical application. These limitations suggest that many Islamic financial products still operate within a legalistic framework rather than fully embodying ethical objectives. This study implies that strengthening governance, enhancing transparency, and integrating value-based intermediation principles are essential to ensure that IMBT contributes effectively to achieving the higher objectives of Shariah and advancing a more just and sustainable financial system.